ДОСЛІДЖЕННЯ ФІЗИЧНИХ ПРОЦЕСІВ У ТОРЦЕВІЙ ЗОНІ ТУРБОГЕНЕРАТОРА ПРИ МЕХАНІЧНИХ УШКОДЖЕННЯХ КРІПЛЕННЯ ОСЕРДЯ СТАТОРА - Кучинський, К.А.; Крамарський, В.А.; Хвалін, Д.І.; Мистецький, В.А. (Інститут електродинаміки Національної академії наук України, 2020)
With the help of mathematical simulation of mechanical processes in the stator core fastening system of a powerful turbogenerator end zone obtained appropriateness of basic parameters changes at the break of clamp prisms heads of the stator core. It is determined that the sudden break of one or more clamp prisms leads to longitudinal oscillation of their other working heads and stiff connected with them press plate, accordingly. Although such oscillation is insignificant but propagates along the entire surface of the press plate with a maximum value in the break zone and subsequent decrease with distance from this zone and therefore can be detected with the help of existing vibration sensors by installing them on the press plate. It is possible to use a limited number of sensors due to the propagation of vibration along the entire surface of the plate. But because the vibration changes are insignificant, in this case, there is a complexity of control that requires the use of high-sensitivity sensors and great informative computing equipment. According to the sensors indices, it is possible to determine the number of breaks for clamp prisms heads of the stator core and the number of them working heads, accordingly. Besides, this effect can be used to diagnose the un-compression of the stator core tooth zone. Since one of the important ways to improve the control and diagnostics of turbogenerators is the detection, the presence of such knowledge will allow making the optimal decision for further measures. Ref. 8, fig. 8, tables 2.